ANALYSIS OF CHANGES IN SHARIA FINANCING AND CONVENTIONAL CREDIT BY ECONOMIC ACTIVITY PER SECTORAL DISTRIBUTION OF COMMUNITY BEFORE AND TIME OF COVID-19, ON THE PERFORMANCE OF SHARIA BANK AND CONVENTIONAL BANK IN INDONESIA - Anwar Sanusi (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to analyze changes in sharia financing and conventional credit according to economic activity per sectoral distribution of society, on the performance of Islamic banks and conventional banks in Indonesia. Data collection techniques by means of documentation studies. The data used in this study is secondary data taken and processed from the Indonesian Banking Statistics Report of the Financial Services Authority, 2005 to 2020. State Owned Banks Operations. The research uses the Autoregressive Distributed Lag (ARDL) panel regression data analysis model and the Difference Test. The results of the panel research, leading indicators of profit for Islamic banks, in the agriculture, forestry, hunting and fishing sectors; manufacturing; electricity; construction; transportation; and conventional banks, in the manufacturing sector; construction; trades; restaurants and hotels; transportation, warehousing and communications; everything in the long run affects the profit The results of the Difference Test analysis, in Islamic Banks there are no significant differences in profit variables before and during Covid-19, Conventional Banks there are significant differences in profit variables before and during the Covid-19 pandemicKeywords: Covid-19, Bank, Credit, Profit.